Experiential Marketing Dengan Pendekatan Sapta Pesona Terhadap Minat Wisatawan Pantai Indah Bosowa Untuk Berkunjung Kembali - Tasrik, Tasrik; Budiandriani , Budiandriani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Sapta Pesona (Seven Charms) strategy approach, which incorporates the seven charms of Indonesian tourism, namely safety, order, cleanliness, coolness, beauty, friendliness, and memories at Pantai Indah Bosowa Makassar, this research intends to find out how far the experiential marketing implementation conducted. By using methods surveys and observation to gather data, the research approach is quantitative and descriptive. According to the study's findings five of the seven charms namely security, cleanliness, coolness, beauty, and memories have all been fully implemented , but two of them has not yet achieved fully implemented such as order and friendliness at Pantai Indah Bosowa Makassar.